A Rare Case of Nasopharyngeal Pleomorphic Adenoma - S. Berrettini; S. Fortunato; A. De Vito; L. Bruschini (Case Reports in Otolaryngology)
Salivary gland tumors are rare. The majority of these tumors are benign and about 70% are pleomorphic adenomas (PA). Nasopharynx is an unusual site for the PA tumor. Only six cases are presented in the literature from 1990 to 2011. The diagnosis of this disease is linked to the sum of imaging tests, clinical and histological study of the mass of the above. The radiologic features of noninvasion of surrounding structures give the first clue to the benign lesion. From the review of the literature and our experience is identified as the gold standard in surgical treatment for this condition. Thanks to the endoscopic surgery, we can perform a complete resection of the lesion without damaging adjacent structures. We presented a case of pleomorphic adenoma of nasopharynx with literature review.